Mathematical Connection Research in Indonesia: A Bibliometric Study (2020–2025) - Meyliana Silvina; Rohati Rohati; Ade Kumalasari (MASI Mandiri Edukasi, 2026)
This study aims to analyze the development of publications on mathematical connections in Indonesia from 2020 to 2025. A total of 91 articles were analyzed using a bibliometric approach based on metadata obtained from Google Scholar, SINTA, and national journal databases. The analysis focused on annual publication trends, productive journals and their indexation status, research methods, educational levels examined, and dominant keywords. The findings show an increase in publications over the last five years, especially in 2023–2024. Most articles were published in national journals indexed by SINTA, while publications in international indexed journals remain limited. The dominant research method was qualitative-descriptive (52 articles), followed by quantitative (22 articles), mixed methods (5 articles), R&D (5 articles), and literature review (7 articles). Junior high school/MTs was the most researched education level, with 47 articles, followed by high school with 34, while research at the elementary and higher education levels was still limited. The most dominant keywords used were mathematical connections and mathematical connection ability, along with problem-solving and contextual learning. This study highlights mathematical connections as an important focus in mathematics education research in Indonesia and suggests further exploration across varied education levels and methodologies.